Severe pneumonia caused by human adenovirus type 55 in children - Zhang, Dongwei; Chen, Yi; Shi, Tingting; Fan, Huifeng; Tian, Xingui; Zhou, Rong; Huang, Li; Yang, Diyuan; Lu, Gen (Frontiers in Pediatrics, 2022)
Background: Emerging human adenovirus type 55 (HAdV-55) causes fatal pneumonia in adults. There is a lack of studies on severe pneumonia caused by HAdV-55 in children. Methods: We conducted a retrospective review of pediatric patients hospitalized at Guangzhou Women and Children’s Medical Center with severe pneumonia from 2013 to 2020 who had human adenovirus (HAdV) detected in throat samples or bronchoalveolar lavage fluid using RT-PCR. The presence of HAdV-55 was determined by PCR amplification of the hypervariable regions of the hexon gene. Demographic, clinical, etiological, and outcome data were collected and analyzed. Results: Over the eight-year period, HAdV-55 was detected in three severe and six critical pediatric pneumonia patients. None of the patients had any underlying diseases, and had a median age of 18 months (range, 6-108 months). The male to female ratio was 2:1. All patients presented with fever and cough, and three patients presented with wheezing and diarrhea. Six patients had coinfections with other respiratory pathogens, such as bacteria, Mycoplasma pneumoniae and fungi. Three critical patients developed plastic bronchitis (PB). The median lengths of invasive mechanical ventilation and hospital stay of the critical patients were 10 (8, 28.75) days and 25 (13, 32.25) days, respectively. Three critical patients died, although two of them received extracorporeal membrane oxygenation (ECMO) and blood purification. Three surviving patients developed post-infectious bronchiolitis obliterans (PIBO) at the follow-up. Conclusions: HAdV-55 can cause fatal pneumonia in children, and shows a high rate of co-infection with other respiratory pathogens and a poorer prognosis combined with PB. Thus, HAdV-55 may be an important subtype in patients with HAdV-induced pneumonia who develop PIBO.